Inter- and intra-population genetic variations in Jatropha curcas populations revealed by inter-simple sequence repeat molecular markers - Biabani, Alireza; Yusop, Mohd Rafii; Saleh, Ghizan; Latif, Mohammad Abdul (Consiglio per la ricerca in agricoltura e l'analisi dell'economia agraria, 2013)
Inter simple sequence reaction (ISSR) was employed to assess diversity in six Jatropha populations that were collected in Malaysia, Indonesia, the Philippines and India. A total of 144 accessions (24 accessions per population) were selected and analysed with 10 ISSR primer combinations to generate a total of 143 polymorphic fragments. The number of bands generated per primer varied from 4 to 27. The percentages of polymorphic bands for the Indonesia1, Indonesia2, Malaysia1, Malaysia2, Philippines and India Jatropha populations were 54.6, 59.4, 46.2, 53.2, 60.8 and 56.4%, respectively, with an average of 55.1%. The Nei's total genetic diversity (HT), the intra-populations genetic diversity (HS) and the coefficient of genetic differentiation (GST) were 0.1136, 0.0989 and 0.1295, respectively. The coefficient of genetic differentiation (GST) was 0.1295, which indicated a frequency of approximately 13% in genetic variations observed in the inter-Jatropha populations, while an 87% variation corresponded to the intra-Jatropha populations. Analysis of molecular variance (AMOVA) analysis indicated highly significant (p ≤ 0.001) genetic differences among the six Jatropha populations. An UPGMA dendrogram was constructed, and the Jatropha populations were grouped into four major clusters at a coefficient level of 0.28. The genetic similarities between the populations ranged from 0.31 to 0.25. The principal component analysis showed a relatively similar grouping of the populations. To obtain high heterotic responses, hybridisation should be made between the two distant populations of Malaysia 1 and Indonesia1.